2016
DOI: 10.2147/cia.s101832
|View full text |Cite
|
Sign up to set email alerts
|

Do fall-risk-increasing drugs have an impact on mortality in older hip fracture patients? A population-based cohort study

Abstract: Objective: The aim of this study was to assess the mortality in hip fracture patients with regard to use of fall-risk-increasing drugs (FRIDs), by comparing survival in exposed and nonexposed individuals. Design: This was a general population-based cohort study. Settings: Data on hip fracture patients were retrieved from three national databases. Participants: All hip fracture patients aged 60 years or older in a Swedish county in 2006 participated in this study. Measurements: We studied the mortality in hip f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Antibiotics like gyrase inhibitors and diuretics increase the risk of dizziness [2325], although a use was observed in less than 10% of the patients treated with CTC. Benzodiazepines and opioids are frequently used in the pre- and postoperative stage and of undisputed benefit for anxiety and pain relief, yet they should be stopped as soon as possible because of their large potential to induce falls and therefore their impact on mortality [2628]. Numerous studies on NSAIDs show their negative impact on cardiovascular system and the increased risk for major bleedings, despite intake of proton-pump inhibitors [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics like gyrase inhibitors and diuretics increase the risk of dizziness [2325], although a use was observed in less than 10% of the patients treated with CTC. Benzodiazepines and opioids are frequently used in the pre- and postoperative stage and of undisputed benefit for anxiety and pain relief, yet they should be stopped as soon as possible because of their large potential to induce falls and therefore their impact on mortality [2628]. Numerous studies on NSAIDs show their negative impact on cardiovascular system and the increased risk for major bleedings, despite intake of proton-pump inhibitors [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective cohort study found that inappropriate prescribing increased three-year risk of mortality post-fracture by 28%, as measured by the screening tool of older people’s prescriptions (STOPP) and screening tool to alert to right treatment (START), [10]. A recent study identified that fall-related medications and polypharmacy were both associated with mortality after hip fracture [23]. Each of these studies examined an older and much more cognitively impaired cohort than is included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have assessed the association between FRIDs and outcomes such as injurious falls and hip fractures 16‐18 . Fewer studies have been conducted to assess the impact of FRID prescribing on fall‐related mortality in among older adults 19 …”
Section: Introductionmentioning
confidence: 99%